Effectiveness of group rebt in reducing irrational beliefs in two groups of Iranian female adolescents living in Kuala Lumpur / Tayebeh Najafi - Najafi, Tayebeh (2012)
The main purpose of this research is to study the effectiveness of group REBT in reducing irrational beliefs in two groups of Iranian female adolescents living in Kuala Lumpur. A number of 40 Iranian female adolescents participated in the study. The participants were assigned to two experimental and two control groups randomly. This study used the pre-test and post-test, by using Jones’ Irrational Beliefs Test (Jones, 1969). Therapeutic sessions were held in 5 consecutive weeks, with two sessions a week. Each session lasted 90 minutes. The data were analyzed through the following statistical measures: (1) Gain Score Analysis (GSA); (2) Independent t-test; and (3) Paired t-test. The following conclusions are drawn from the study: First, the study indicates that comparing the experimental group and the control group of 12-14 year old adolescents, group REBT significantly reduced the following irrational beliefs in the experimental group: Approval from Others, Self Expectation, Emotional Control, Reaction to Frustration, Helplessness about Changing, Avoiding Problems, Concern about Future Problems, Relying on Others, Blaming, and Perfectionism. Second, the study indicates that group REBT has significantly reduced irrational beliefs in the experimental group of 12-14 year old adolescents. Third, the study indicates that group REBT has significantly reduced irrational beliefs in the experimental group of 18-20 year old adolescents. Fourth, the study indicates that comparing the experimental group and the control group of 18-20 year old adolescents, group REBT significantly reduced the following irrational beliefs in the experimental group: Approval from Others, Concern about Future Problems, Emotional Control, Reaction to Frustration, Blaming, Self Expectation, Helplessness about Changing, Avoiding Problems, Perfectionism, and Relying on Others. Fifth, the study indicates that the treatment has been effective more in the 12-14 year old group. In conclusion, group REBT has been effective in reducing irrational beliefs in Iranian female adolescents living in Kuala Lumpur. Based on the findings of this study, it is suggested that educational settings provide group counseling, especially for younger adolescents living abroad. Moreover, it is suggested that cognitive-behavior programming be integrated as a part of classroom curriculum.